1991
DOI: 10.1111/j.1346-8138.1991.tb03162.x
|View full text |Cite
|
Sign up to set email alerts
|

Hair Growth on Nude Mice Due to Cyclosporin A

Abstract: One of the most common dermatological side effects of cyclosporin A (CsA) is dose-dependent hypertrichosis. Similar hair growth was noted in nude mice in an attempt to increase the acceptance of human xenografts with CsA in the T-cell-deficient congenitally athymic nude (nu/nu) mice. The aim of the present study was to further investigate the stimulation of hair growth on nude mice not only by oral administration of CsA but also by topical and subcutaneous administration of CsA. Young BALB/c female nude mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In vivo studies by Watanabe et al , showed that CsA treated FOXN1 deficient (nude) mice overcome some aspects of FOXN1 deficiency, that is, they displayed hair re-growth [17]. In a follow up study they showed that this phenomenon may involve PKC, whose high activity in nude skin is suppressed by CsA treatment [18].…”
Section: Resultsmentioning
confidence: 99%
“…In vivo studies by Watanabe et al , showed that CsA treated FOXN1 deficient (nude) mice overcome some aspects of FOXN1 deficiency, that is, they displayed hair re-growth [17]. In a follow up study they showed that this phenomenon may involve PKC, whose high activity in nude skin is suppressed by CsA treatment [18].…”
Section: Resultsmentioning
confidence: 99%
“…CsA has been also previously shown to induce hair growth both in nude (48) and normal mice (31,34). Our experimental data support these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Skin specimens of the CZ-treated mice were also found to have abundant BrdU-positive keratinocytes in their hair bulbs and outer root sheaths. One hypothesis is that temporary keratinization in the HF gives strength to hair shafts that rise above the skin surface (Watanabe et al, 1991). Moreover, in this study we have closely observed two generations of hair growth, as well as macroscopic analysis of hair growth parameters that included changing patterns of nude mice hair growth, area of hair coverage, and length of hair shaft.…”
Section: Discussionmentioning
confidence: 61%